Impact of Bullying on Social-Emotional Behavior in Elementary School Students: A Qualitative Case Study at SD Negeri 115 Palembang, Indonesia - Sari, Herlina; Rosani, Meilia; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2025)
This qualitative case study analyzes the impact of bullying on social-emotional behavior among students (N=11) at SD Negeri 115 Palembang, Indonesia, using observation, interviews, and documentation (March–June 2025). The findings reveal significant social and emotional consequences, including social withdrawal, aggression, reduced self-confidence, isolation, disrupted class dynamics, and increased dropout risk. Emotionally, students exhibited anxiety, depression, low self-esteem, anger, stress, and sleep disturbances. Novel solutions were identified, such as counseling for emotional support, fostering a secure school environment, promoting positive peer interactions, forming anti-bullying task forces, integrating character education, involving parents in recovery, and implementing regular monitoring. The study contributes to the literature by highlighting the multifaceted effects of bullying in an Indonesian elementary school context and offering actionable strategies for mitigation. Practical implications include the adoption of holistic anti-bullying programs that combine psychosocial support, peer involvement, and parental engagement to restore students’ social-emotional well-being. This research underscores the urgency of institutional interventions to create safer, more inclusive educational environments.